Analisis Perilaku Konsumsi Masyarakat pada Event dan Konser di Kalangan Mahasiswa di Kota Surakarta - Mahadewi, Nabila; Oktavianingtyas, Ardhini; Suyadi, Auliya A. P.; Barlian, Aurellia D.; Rizqia, Elfatiya; Wulandari, Mutiah; Sita, Nadila A.; Aisy Q.H, Rohadatul; Marrelda, Sahda A.; Lestari, Yunita A. (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
The increasing number of concerts and events in Surakarta has heightened public interest, particularly among university students. However, the organization of these concerts and events indirectly leads to a change in student behavior, making them more consumptive. The purpose of this research is to understand the consumption behavior of the community and its impact on participation in events and concerts in Surakarta. This study uses Jean Baudrillard's theory of consumer society and Theodor Adorno's theory of the culture industry. The research employs a qualitative method with a phenomenological approach. The findings of this study reveal that the consumption behavior and the impact of organizing concerts and events make students more consumptive, as evidenced by the increased purchase of tickets and food, as well as additional expenses incurred to maintain their lifestyle.